Changes in Plasma Metabolites Concentrations in Obese Dogs Supplemented With Anti-oxidant Compound - Kawasumi, Koh; Murai, Tae; Mizorogi, Takayuki; Okada, Yuki; Yamamoto, Ichiro; Suruga, Kohei; Kadokura, Kazunari; Arai, Toshiro (Frontiers in Nutrition, 2018)
The aim of this study is to discuss the effect of anti-oxidant supplement (Rv-PEM01-99, Kibun Foods, Inc., Tokyo, Japan) on changes in energy metabolism in obese dogs. 200 mg/kg/day of Rv-PEM01-99 (equivalent to 5 mg kg/day of quercetin derivative) were applied for 6 weeks to the Beagle dogs fed high fat diet (HFD) or control diet (CD). In the present study, body weight (BW) decreasing effect of Rv-PEM 01-99 in obese dogs was not clear. However, plasma alkaline phosphatase (ALP) activities at the end of experiment were significantly decreased compared to those at the start of experiment in obese dogs supplemented with Rv-PEM 01-99 (paired-t test, p < 0.05). In control dogs supplemented with Rv-PEM 01-99, Plasma malondialdehyde (MDA), and triglycerides (TG) levels and lactate dehydrogenase (LDH) activities were significantly decreased compared to those at the start of experiment (paired-t test, p < 0.05). From these findings, Rv-PEM 01-99 seems to be not harmful for dogs. Anti-lipid peroxide effect and liver function improvement are expected in the dogs supplemented with Rv-PEM 01-99.